2021
DOI: 10.5603/cj.a2019.0037
|View full text |Cite
|
Sign up to set email alerts
|

Poor long-term outcome in acute coronary syndrome in a real-life setting: Ten-year outcome of the TACOS study

Abstract: Background: Long-term outcome of the three categories of acute coronary syndrome (ACS) in real-life patient cohorts is not well known. The objective of this study was to survey the 10-year outcome of an ACS patient cohort admitted to a university hospital and to explore factors affecting the outcome. Methods: A total of 1188 consecutive patients (median age 73 years) with ST-elevation myocardial infarction (STEMI), non-ST-elevation myocardial infarction (NSTEMI) or unstable angina pectoris (UA) in 2002-2003 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…74 Nevertheless, arguably the most suitable comparators are patients with acute myocardial infarction due to similar comorbidities and overlapping origins. 75,76 Studies 75,77,78 based on older data sets reported 10-year survival rates of discharged patients with ST-elevation myocardial infarction (STEMI) of approximately 50%. A newer study 79 reports a 10-year survival of 76.2%.…”
Section: Discussionmentioning
confidence: 99%
“…74 Nevertheless, arguably the most suitable comparators are patients with acute myocardial infarction due to similar comorbidities and overlapping origins. 75,76 Studies 75,77,78 based on older data sets reported 10-year survival rates of discharged patients with ST-elevation myocardial infarction (STEMI) of approximately 50%. A newer study 79 reports a 10-year survival of 76.2%.…”
Section: Discussionmentioning
confidence: 99%
“…As far as the accepted liver-based screening criteria for CCT are concerned, it appears that a significant group of patients may be excluded from dedicated clinical trials. Moreover, the rest of participants may not be representative of the real-world population with the disease [12][13][14]. On the other hand, recent evidence suggests that elevated serum transaminases are associated with more severe myocardial damage along with worse short-and long-term clinical outcomes [6,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, preserving renal function in coronary artery disease patients should be considered a priority. 37 The intracranial bleeding rate was low, being seen in 1 patient. This patient improved after the evacuation of the clot by a neurosurgeon and subsequently came for follow-up.…”
Section: Managing Groin Hematomasmentioning
confidence: 91%